Next-Generation Probiotics: health-promoting bacteria of the human gut - Golić, Nataša; Djokić, Jelena; Tolinački, Maja; Živković, Milica (Archives of Pharmacy, 2023)
In recent years, a vast number of human diseases have been correlated with gut microbiota dysbiosis. The development of modern methods in molecular microbiology, such as the culturomics approach, as well as various multi-omics methods like next generation sequencing, transcriptomics and metabolomics analysis, coupled with large data sets correlation analysis, enabled the cultivation and characterization of novel anaerobic hitherto uncultivated Next-Generation Probiotics. In addition, the results of host-microbe interactions studies helped to reveal the mechanisms involved in the beneficial effects of Next-Generation Probiotics. Eventually, the obtained data on Next-Generation Probiotics will help to broaden the scientific knowledge on these bacteria, in terms of both their safety and health-promoting effects, unravel opportunities for the development of novel therapeutic strategies for prevention and treatment of tumors, metabolic, neuropsychiatric and other diseases, with the aim of relieving the symptoms of the diseases and increasing the quality of life for patients and their families. So far, the best characterized probiotics of the new generation are Akkermansia muciniphila, Faecalibacterium prauznitzii and Bacteroides fragilis.